Psychological Meaning of the Constructs Dating, Fuckfriends and Free in Pachucas’s Young People - García Meraz, Melissa (Consorcio de Universidades Mexicanas A.C., 2014)
In order to identify the psychological meaning of the constructs: boy/girlfriend, fuckfriend, and free a questionnaire was administrated, following the semantic networks technique (Figueroa, Gonzáles, & Solís, 1981), but the procedure selected was proposed by Reyes (1993). The questionnaire was applied to a 230 participants, in which 32 of the participants had a relationship called as fuck friend, 29 had a relationship called free, 74 were in a courtship and 95 had no relationship. The instruments were applied individually and collectively in different schools in the municipality of Pachuca, Hidalgo; in all the cases anonymity was ensured. The results show that the stimulus fuck friend is defined by words like friendship, love, fun, understanding, and trust. The concept of a free is defined by aspects such as freedom, sex, friendship, fun and “no”. While boyfriends stimulus is defined by words like love, affection, honesty, respect, understanding and friendship. As mentioned Miller, Vandome and McBrewster (2010), casual relationships and casual sex are different. In relationships that are described as casual sex, there is no emotional interest by the person, they are not friends, and they do not give affection or love. Casual sex is a one night stand. In contrast, people that are involved in fuck friend relationships expect affection and love, the relationship lacks the commitment but not the part of intimacy: love and affection are in an informal relationship. Therefore, the results are discussed in terms of cultural and social changes that are present in the beginning and dissolution of relationships.